Il sole e il bene. Funzione e limiti dell’analogia in Resp. VI 505a-509b - Fronterotta, Francesco (ΠΗΓΗ/FONS, 2017)
The presence of analogy in Book VI of Plato’s Republic, conceived as a relationship, horizontal or vertical, of functional equality between heterogeneous domains, offers promising options to understand the status and function of the good itself and in relation to its own “products”. In particular, the image of the Sun as the “son” of the good does not imply that Plato admits an integral generation or a derivation of the first from the second, nor does it suggest an integral derivation of sensible things from intelligible ideas.
Keywords: Republic; good; Sun; analogy; productor/products; ideas; sensible reality